To Study the Correlation Between Transvaginal Sonography and Endometrial Biopsy in Women Presenting with Abnormal Uterine Bleeding - Nasir, Syeda Ansa; Singh, Shweta; Kusumlata, Kusumlata; Khanam, Suraiya (Journal of Neonatal Surgery, 2025)
Background: Abnormal uterine bleeding (AUB) is a prevalent gynecological issue with multiple etiologies, requiring accurate diagnosis for effective management. The prevalence of AUB among reproductive-aged women ranges from 10% to 30%. Transvaginal sonography (TVS) is a first-line, non-invasive diagnostic tool; however, it lacks histopathological confirmation, which is provided by endometrial biopsy (EB). The FIGO PALM-COEIN system classifies AUB causes, but the correlation between TVS and biopsy findings remains uncertain. This study aims to evaluate the diagnostic accuracy and correlation between TVS and EB in AUB cases. Methodology: This prospective observational study was conducted in the Department of Obstetrics and Gynecology at a tertiary health care centre, Lucknow, over 18 months. A total of 175 women aged ≥35 years with AUB underwent clinical assessment, TVS for endometrial thickness measurement, and EB for histopathological evaluation. Statistical analysis using SPSS 22.0 was performed. Results: Among 175 patients (mean age 45.50 ± 18.27 years; range: 25–64 years), TVS detected abnormalities in 73.1% of cases, with fibroids (23.4%) and adenomyosis (18.9%) being most common. Endometrial hyperplasia (57.7%) was the predominant histopathological finding, followed by polyps (36.6%) and carcinoma (1.1%). A significant correlation (p < 0.001) was observed between TVS findings and biopsy results, particularly in cases with heavy menstrual flow, irregular cycles, and increased endometrial thickness. Conclusion: In conclusion, TVS serves as a valuable, non-invasive diagnostic tool, while EB remains essential for definitive diagnosis, especially in high-risk cases. The combined use of both modalities enhances diagnostic accuracy, facilitating timely and effective AUB management